Characterization of thoracic spinal manipulation and mobilization forces in older adults. (October 2021) - Funabashi, Martha; Son, James; Pecora, Cosma Gary; Tran, Steve; Lee, Joyce; Howarth, Samuel J.; Kawchuk, Gregory; de Luca, Katie
Abstract: Background: Spinal mobilization and spinal manipulation are common interventions used by manual therapists to treat musculoskeletal conditions in older adults. Their force-time characteristics applied to older adults' thoracic spine are important considerations for effectiveness and safety but remain unknown. This study aimed to describe the force-time characteristics of posterior-to-anterior spinal mobilization and manipulation delivered to older adults' thoracic spine. Methods: Twenty-one older adults (≥65 years) with no thoracic pain received posterior-to-anterior thoracic spinal mobilization and/or manipulation with the force characteristics a chiropractor deemed appropriate. Six-degree-of-freedom load cells and an instrumented treatment table recorded the force characteristics of both interventions at the clinician-participant and participant-table interfaces, respectively. Preload force, total peak force, time to peak and loading rate were analyzed descriptively. Findings: Based on data from 18 adults (56% female; average: 70 years old), mean resultant spinal mobilization forces at the clinician-participant interface were: 220 ± 51 N during preload, 323 ± 67 N total peak force, and 312 ± 38 ms time to peak. At the participant-table interface, mobilization forces were 201 ± 50 N during preload, 296 ± 63 N total peak force, and 308 ± 44 ms time to peak. Mean resultant spinal manipulation forces at the clinician-participant interface were: 260 ± 41 N during preload, 470 ± 46 N total peak force, and 165 ± 28 ms time to peak. At the participant table interface, spinal manipulation forces were 236 ± 47 N during preload, 463 ± 57 N total peak force, and 169 ± 28 ms time to peak. Interpretation: Results suggest older adults experience unique, but comparable force-time characteristics during spinal mobilization and manipulation delivered to their thoracic spine compared to the ones delivered to younger adults described in the literature. Highlights: Two common manual interventions' force-time characteristics applied to older adults are described. On average, peak forces of 296 N to 323 N were recorded during spinal mobilization. On average, peak forces of 463 N to 470 N were recorded during spinal manipulation. Older adults experience unique forces compared to the ones reported in younger adults.